The Influence of Human Resources Factors on Employee Performance at BRI Bukittinggi Branch - Febby Valeriana Putri; Firwan Tan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Bank Rakyat Indonesia (Persero) Tbk is the first government-owned bank to operate in Indonesia. The goals and objectives of BRI are outlined in its vision and mission to serve customers. Bank Rakyat Indonesia (BRI) is one of the largest state-owned banks in Indonesia. This study aims to examine the impact of Human Resources Factors on Employee Performance at BRI Bukittinggi Branch. The research method used is quantitative. The sample for this study consists of all employees at BRI Bukittinggi Branch, totaling 87 individuals. The results of the study indicate a positive and significant impact of work competency on employee performance at BRI Bukittinggi Branch. There is a positive and significant impact of work commitment on employee performance at BRI Bukittinggi Branch. There is a positive and significant impact of work discipline on employee performance at BRI Bukittinggi Branch. There is a positive but not significant impact of work training on employee performance at BRI Bukittinggi Branch.